Hypokalemia and sudden cardiac death in people without structural heart disease: Case presentation and systematic review - Meregildo-Rodriguez, Edinson Dante (2022)
Introduction: The aim of this study was to synthesize the evidence on the causes of sudden cardiac death (SCD) associated with hypokalemia in individuals ≥15 to <65 years of age without structural heart disease. Case report. We reported a case and collected SCD cases following the PECO strategy. We conducted a bibliographic search of the literature published up to November 30, 2021. We included 25 cases. The mean age was 33.8 ± 2.4 years. Of the total cases, 60% were male and 60% corresponded to acquired etiologies. Thyrotoxicosis was the etiology of 8% of cases. The QTc interval was prolonged in 90% of the cases in which it could be recorded. Sixty percent of cases occurred out of hospital. Only 24% of episodes resulted in death. Conclusions. Thyrotoxicosis is a rare cause of hypokalemic sudden cardiac arrest (SCA). Hypokalemic SCA seems to be associated with better clinical results compared to SCA associated with hyperkalemia or normokalemia.